Anticoagulant Treatment for Splanchnic Vein Thrombosis in Liver Cirrhosis: A Systematic Review and Meta-Analysis - Valeriani, Emanuele; Di Nisio, Marcello; Riva, Nicoletta; Cohen, Omri; Porreca, Ettore; Senzolo, Marco; De Gottardi, Andrea; Magaz, Marta; Garcia-Pagan, Juan-Carlos; Ageno, Walter (Thrombosis and Haemostasis, 2021)
Background Splanchnic vein thrombosis (SVT) is a common complication in patients with liver cirrhosis. The aim of this study was to evaluate the efficacy and safety of anticoagulant therapy for SVT in cirrhotic patients.Methods In this systematic review and meta-analysis, studies reporting on SVT recanalization and progression, recurrent venous thromboembolism (VTE), major bleeding, and overall mortality were searched in MEDLINE, EMBASE, and ClinicalTrial.gov up to December 2019. Pooled proportions and risk ratios (RRs) with corresponding 95% confidence intervals (CIs) were calculated.Results A total of 1,475 patients were included in 26 studies (23 observational and 3 randomized controlled trials). In patients receiving anticoagulant therapy, SVT recanalization occurred in 68% (95% CI, 62–74; 571/842 patients; 22 studies), SVT progression in 6% (95% CI, 4–9; 25/748 patients; 22 studies), recurrent VTE in 10% (95% CI, 4–22; 48/399 patients; 7 studies), major bleeding in 6% (95% CI, 4–10; 58/785 patients; 18 studies), and overall mortality in 9% (95% CI, 6–14; 68/787 patients; 17 studies). Anticoagulant treatment was associated with higher SVT recanalization (RR 3.19; 95% CI, 1.42–7.17), lower thrombosis progression (RR 0.28; 95% CI, 0.15–0.52), major bleeding (RR 0.52; 95% CI, 0.28–0.97), and overall mortality (RR 0.42; 95% CI, 0.24–0.73) compared with no treatment.Conclusion Anticoagulant therapy seems to improve vein recanalization and to reduce SVT progression, major bleeding, and overall mortality in cirrhotic patients with SVT. The incidence of recurrent VTE during anticoagulation remains substantial.
Keywords: anticoagulants; liver cirrhosis; portal vein; splanchnic circulation